Ceramic burner multilayer composite prefabricated brick for hot blast stove and preparation method of ceramic burner multilayer composite prefabricated brick

By adopting a multi-layer composite prefabricated brick structure in ceramic burners, it is divided into high-temperature compression-resistant working layer and low-thermal insulation layer. Combined with secondary molding and Mullechemical reaction, the problems of heat leakage and short service life in the refractory brick masonry of existing ceramic burners are solved, achieving longer service life and higher durability.

CN119638384APending Publication Date: 2025-03-18ZHENGZHOU ANNEC IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411907007.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The refractory brick masonry of existing ceramic burners has problems such as many brick joints, severe heat leakage, and short service life. The masonry quality is difficult to control and bricks are prone to falling.

Method used

It adopts a multi-layer composite prefabricated brick structure, which is divided into a working layer and an insulating layer. The working layer has high temperature compression resistance, flexural strength and stable chemical properties. The insulation layer has low thermal conductivity and thermal stability. It enhances the corrosion resistance and thermal stability of the materials through secondary molding and mullet chemical reactions.

Benefits of technology

It extends the service life of the hot air furnace, improves the compressive, flexural strength and chemical stability of the burner, and reduces the number of repairs and cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a multilayer composite prefabricated brick of a ceramic burner for a hot blast stove, which comprises the following components in parts by weight: 30-40 parts of 45 alumina clinker, 10-20 parts of flint clay, 20-50 parts of 84 alumina clinker, 5-20 parts of fused white corundum, 1-10 parts of andalusite, 1-10 parts of clay waste brick powder, 0.2-0.5 part of first-grade clay powder, 1-5 parts of silica powder, 1-10 parts of CA-50 aluminate cement and 0.5-1 part of activated alumina micro powder. The addition amount of the sodium tripolyphosphate is 0 to 0.02 percent of the total weight of the raw materials. The hot blast stove is divided into the working layer and the heat preservation layer, the working layer has good high-temperature compression resistance and breaking strength and good heat stability and chemical performance stability, and the heat preservation layer has low heat conductivity and good heat stability, so that the service life of the hot blast stove is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a ceramic burner multi-layer composite prefabricated brick for a hot blast furnace and a preparation method thereof. Background Art

[0002] The structural type and operating system of the burner have a great impact on the operation of the blast furnace hot blast stove. At present, ceramic burners are generally used in large and medium-sized blast furnace hot blast stoves. This type of ceramic burner is built with refractory materials in the combustion chamber, and the operation is periodic. The temperature fluctuates by about 600°C, and is affected by air flow scouring and chemical erosion, and the working conditions are poor. The furnace body built with refractory bricks has many brick joints and is prone to heat leakage. In addition, the refractory brick masonry burner requires more than 20,000 bricks, and there are many brick joints, which are prone to heat leakage. Since the furnace roof is arc-shaped and the brick shape is complex, the masonry quality is difficult to control, and bricks are easy to fall off during use. Therefore, in order to extend the service life of the hot blast stove burner, it is necessary to develop a multi-layer composite prefabricated brick for a ceramic burner for a hot blast stove. Summary of the invention

[0003] In order to solve the deficiencies in the prior art, the present invention provides a multi-layer composite prefabricated brick for a ceramic burner for a hot blast furnace, which is divided into a working layer and a thermal insulation layer. The working layer has good high-temperature compressive and flexural strength, good thermal stability and chemical stability, and the thermal insulation layer has low thermal conductivity and good thermal stability, thereby extending the service life of the hot blast furnace. In order to achieve the above object, the technical solution adopted by the present invention is: The added weight portions of the invention are: 30-40 parts of 45 alumina clinker, 10-20 parts of coke gemstone, 20-50 parts of 84 alumina clinker, 5-20 parts of fused white corundum, 1-10 parts of andalusite, 1-10 parts of clay waste brick powder, 0.2-0.5 parts of primary clay powder, 1-5 parts of silicon powder, 1-10 parts of CA-50 aluminate cement, 0.5-1 parts of activated alumina powder, 0.3-0.5 parts of CA-70 aluminate cement, and the added amount of sodium tripolyphosphate is 0-0.02% of the total weight of the original material.

[0004] The particle size of the 45 alumina clinker is 8-4 mm, wherein the weight fraction of Al2O3 is ≥45%; The particle size of the coke gemstone is 4-0 mm, wherein the weight fraction of Al2O3 is ≥45%; The particle size of the 84 alumina clinker is a mixture of 8-5mm, 3-1mm and ≥0.088mm, the mixing ratio is 1:1:1, and the weight fraction of Al2O3 is ≥84%; The fused white corundum has a particle size of 5-3 mm and ≥0.045 mm, the mixing ratio is 2:1, and the weight fraction of Al2O3 is ≥99.5%; The particle size of the andalusite is 1-0 mm, wherein the weight fraction of Al2O3 is ≥55%; The particle size of the clay waste brick powder is ≥0.088 mm, wherein the weight fraction of Al2O3 is ≥50%; The particle size of the primary clay powder is ≥0.088 mm, wherein the weight fraction of Al2O3 is ≥50%; The particle size of the silicon powder is ≥5 μm; The particle size of the CA-50 aluminate cement is ≥0.074 mm, wherein the weight fraction of Al2O3 is ≥50%; The particle size of the activated alumina powder is ≥3 μm, wherein the weight fraction of Al2O3 is ≥99.5%; The particle size of the CA-70 aluminate cement is ≥0.074 mm, wherein the weight fraction of Al2O3 is ≥70%.

[0005] The preparation method of the ceramic burner multilayer composite prefabricated brick for hot blast furnace of the present invention is as follows: Step 1: Weigh and mix 45 alumina clinker with a particle size of 8-4mm and coke gemstone with a particle size of 4-0mm according to the above ratio, and put them into the mixing equipment; Step 2: Weigh and mix the clay waste brick powder with a particle size of ≥0.088 mm, the first-grade clay powder with a particle size of ≥0.088 mm, and the CA-50 aluminate cement with a particle size of ≥0.074 mm according to the above proportions, add half of the sodium tripolyphosphate and the silicon micropowder with a particle size of ≥5 um according to the above proportions, and mix in a premixer for 1-2 minutes to obtain a fine powder mixture; Step 3: Add the fine powder mixture obtained in step 2 to the stirring device in step 1, add tap water and stir for 1-2 minutes to obtain a mixture for the insulation layer; Step 4: Weigh and mix 84 alumina clinker with a particle size of 8-5mm, fused white corundum with a particle size of 5-3mm, 84 alumina clinker with a particle size of 3-1mm, and andalusite with a particle size of 1-0mm according to the above proportions, and put them into a stirring device; Step 5: Weigh and mix 84 alumina clinker with a particle size of ≥0.088mm, fused white corundum with a particle size of ≥0.045mm, activated alumina powder with a particle size of ≥3um, and CA-70 aluminate cement with a particle size of ≥0.074mm according to the above proportions, add the remaining half of sodium tripolyphosphate and silicon powder with a particle size of ≥5um, and mix in a premixer for 1-2 minutes; Step 6: Add the fine powder matrix premixed in step 5 to the stirring device in step 4, add an appropriate amount of pure tap water and stir for 1-2 minutes to obtain a working layer mixture; Step 7: Pour the material obtained in step 6 into the mold to 1 / 2 capacity, and vibrate to form it as the working layer. Step 8: Pour the material obtained in step 3 into the remaining 1 / 2 capacity of the mold and vibrate it to form a heat-insulating layer. Step nine, drying at 100-150°C for 24 hours to obtain the ceramic burner multi-layer composite prefabricated brick for hot blast furnace.

[0006] The present invention innovatively divides the prefabricated bricks into a working layer and a thermal insulation layer. The working layer has good high-temperature compression and flexural strength, good thermal stability and chemical stability, and the thermal insulation layer has low thermal conductivity and good thermal stability, which prolongs the service life of the hot air furnace. The present invention adopts secondary molding, with the working layer mixture at the bottom layer and the insulation layer mixture at the upper layer, so that the working layer can be more compact and have stronger corrosion resistance. More importantly, the fusion of the working layer and the insulation layer can be more compact. Since the insulation layer contains primary clay at the fusion of the working layer and the insulation layer, the excess Al2O3 in the corundum clinker of the working layer undergoes mullite with the clay under the high temperature of the use environment, so that the separated SiO2 undergoes secondary mullite. In the high temperature environment of use, a mullite layer is formed between the working layer and the insulation layer. When the working layer is eroded, the mullite layer can resist the erosion of the use environment and protect the insulation layer, thereby increasing the service life of the invention and reducing the number of maintenance times of the user unit. At the same time, the raw materials of Jiaobaoshi contain a large number of micropores. Under thermal shock, the length of the internal cracks of the cast bricks becomes shorter. At the same time, the CA-50 cement in the cross layer makes up for the shortcomings of CA-70 cement, which has slow hydration and hardening and low early strength, and prevents the cross layer from delamination and cracking.

[0007] The andalusite used in the present invention is gradually mullitized under the high temperature environment of use, and the generated SiO2 further forms secondary mullite in situ with the added alumina micropowder; the columnar and needle-shaped mullite have an interlaced network structure, which increases the strength of the material, and the expansion effect produced by the secondary mullitization offsets the shrinkage of the material under high temperature, effectively improves the load softening temperature of the material, and makes the material have good thermal shock stability and erosion resistance; in the secondary mullitization stage, sintering has begun to occur due to the formation of a liquid phase, but the process is slow. When the secondary mullitization is completed, the recrystallization sintering effect begins to proceed rapidly. Under this effect, the porosity is reduced and the material tends to be dense.

[0008] In step 2 and step 5, the coarse material and the fine material are mixed respectively. Premixing the matrices of different particle sizes in advance can make the raw materials fully mixed and uniform, avoid errors and unevenness caused by direct mixing, and shorten the time for subsequent mixing of the coarse material and the fine material. Finally, the premixed fine powder is added to the premixed coarse powder, stirred and mixed, and the final refractory material can be obtained.

[0009] High alumina: strong chemical stability and high temperature resistance, ensuring the high temperature resistance, high strength, good high temperature volume stability and corrosion resistance of the refractory material.

[0010] Andalusite: The added andalusite makes the material have the advantages of high temperature resistance, strong thermal shock stability, chemical stability and strong resistance to chemical corrosion.

[0011] Fused white corundum: Fused white corundum has a small thermal expansion coefficient, which can make the thermal expansion of refractory materials smaller and make the stability of refractory materials better.

[0012] Alumina powder: can improve the secondary mullite of andalusite.

[0013] Silicon dioxide powder: reacts with calcium oxide to form calcium silicate, which can improve the strength and high temperature load softening temperature of refractory materials.

[0014] The ceramic burner composite prefabricated bricks for the hot blast furnace are directly baked and used without going through a firing process, and have the advantages of simple process, energy saving, convenient construction, low cost, etc.

[0015] The ceramic burner composite prefabricated brick for hot blast furnace in the present invention has good high temperature compression and flexural strength, good thermal stability and chemical stability. The ceramic burner multilayer composite prefabricated brick is divided into a working layer and a thermal insulation layer. The working layer has good high temperature compression and flexural strength, good thermal stability and chemical stability. The thermal insulation layer has low thermal conductivity and good thermal stability, and the hot blast furnace has a longer service life. The present invention is easy to construct, does not require firing, has obvious economic benefits, forms a technical advantage for manufacturers, has a higher premium, and has a longer service life for the user unit, diluting the use cost. DETAILED DESCRIPTION

[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the protection scope of the present invention.

[0017] In order to more clearly understand the technical content of the present invention, the following examples are given in detail. The weight fraction of 45 clinker Al2O3 in the raw materials used in the following examples is ≥45%, the weight fraction of coke gemstone Al2O3 is ≥45%, the weight fraction of clay waste brick Al2O3 is ≥50%, the weight fraction of primary clay Al2O3 is ≥50%, the weight fraction of CA-50 aluminate cement Al2O3 is ≥50%, the weight fraction of 84 alumina clinker Al2O3 is ≥84%, the weight fraction of fused white corundum Al2O3 is ≥99.5%, the weight fraction of andalusite Al2O3 is ≥55%, the weight fraction of activated alumina powder Al2O3 is ≥99.5%, and the weight fraction of CA-70 aluminate cement Al2O3 is ≥70%.

[0018] Example 1

[0019] The added weight proportions of the raw materials of the present invention are: 30 parts of 45 alumina clinker, 10 parts of coke gemstone, 22 parts of 84 alumina clinker, 5 parts of fused white corundum, 10 parts of andalusite, 10 parts of clay waste brick powder, 0.5 parts of primary clay powder, 1 part of silica powder, 10 parts of CA-50 aluminate cement, 1 part of activated alumina powder, 0.5 parts of CA-70 aluminate cement, and the added amount of sodium tripolyphosphate is 0.01% of the total weight of the raw materials.

[0020] The particle size of 84 alumina clinker is a mixture of 8-5mm, 3-1mm and ≥0.088mm, and the mixing ratio is 1:1:1.

[0021] The particle size of fused white corundum is a mixture of 5-3mm and ≥0.045mm, with a mixing ratio of 2:1.

[0022] The preparation method of the ceramic burner multilayer composite prefabricated brick for hot blast furnace of the present invention is as follows: Step 1: Weigh and mix 45 alumina clinker with a particle size of 8-4mm and coke gemstone with a particle size of 4-0mm according to the above ratio, and put them into the mixing equipment; Step 2: Weigh and mix the clay waste brick powder with a particle size of ≥0.088 mm, the first-class clay powder with a particle size of ≥0.088 mm, and the CA-50 aluminate cement with a particle size of ≥0.074 mm according to the above proportions, add half of the sodium tripolyphosphate and the silicon micropowder with a particle size of ≥5 um according to the above proportions, and mix in a premixer for 1 minute to obtain a fine powder mixture; Step 3: Add the fine powder mixture obtained in step 2 to the stirring device in step 1, add tap water and stir for 2 minutes to obtain a mixture for the insulation layer; Step 4: Weigh and mix 84 alumina clinker with a particle size of 8-5mm, fused white corundum with a particle size of 5-3mm, 84 alumina clinker with a particle size of 3-1mm, and andalusite with a particle size of 1-0mm according to the above proportions, and put them into a stirring device; Step 5: Weigh and mix 84 alumina clinker with a particle size of ≥0.088 mm, fused white corundum with a particle size of ≥0.045 mm, activated alumina powder with a particle size of ≥3 um, and CA-70 aluminate cement with a particle size of ≥0.074 mm according to the above ratio, add the remaining half of sodium tripolyphosphate and silicon powder with a particle size of ≥5 um, and mix in a premixer for 1.5 minutes; Step 6: Add the fine powder matrix premixed in step 5 to the stirring device in step 4, add an appropriate amount of pure tap water and stir for 1 minute to obtain a working layer mixture; Step 7: Pour the material obtained in step 6 into the mold to 1 / 2 capacity, and vibrate to form it as the working layer. Step 8: Pour the material obtained in step 3 into the remaining 1 / 2 capacity of the mold and vibrate it into shape to serve as a heat-insulating layer.

[0023] Step nine, drying at 100°C for 24 hours to obtain the ceramic burner multi-layer composite prefabricated brick for hot blast furnace.

[0024] Example 2

[0025] The added weight proportions of the raw materials of the present invention are: 31 parts of 45 alumina clinker, 15 parts of coke gemstone, 30 parts of 84 alumina clinker, 15 parts of fused white corundum, 5 parts of andalusite, 1 part of clay waste brick powder, 0.2 parts of primary clay powder, 1 part of silica powder, 1 part of CA-50 aluminate cement, 0.5 parts of activated alumina powder, 0.3 parts of CA-70 aluminate cement, and the added amount of sodium tripolyphosphate is 0.01% of the total weight of the raw materials.

[0026] The particle size of 84 alumina clinker is a mixture of 8-5mm, 3-1mm and ≥0.088mm, and the mixing ratio is 1:1:1.

[0027] The particle size of fused white corundum is a mixture of 5-3mm and ≥0.045mm, with a mixing ratio of 2:1.

[0028] The preparation method of the ceramic burner multilayer composite prefabricated brick for hot blast furnace of the present invention is as follows: Step 1: Weigh and mix 45 alumina clinker with a particle size of 8-4mm and coke gemstone with a particle size of 4-0mm according to the above ratio, and put them into the mixing equipment; Step 2: Weigh and mix the clay waste brick powder with a particle size of ≥0.088 mm, the first-grade clay powder with a particle size of ≥0.088 mm, and the CA-50 aluminate cement with a particle size of ≥0.074 mm according to the above proportions, add half of the sodium tripolyphosphate and the silicon micropowder with a particle size of ≥5 um according to the above proportions, and mix in a premixer for 2 minutes to obtain a fine powder mixture; Step 3: Add the fine powder mixture obtained in step 2 to the stirring device in step 1, add tap water and stir for 2 minutes to obtain a mixture for the insulation layer; Step 4: Weigh and mix 84 alumina clinker with a particle size of 8-5mm, fused white corundum with a particle size of 5-3mm, 84 alumina clinker with a particle size of 3-1mm, and andalusite with a particle size of 1-0mm according to the above proportions, and put them into a stirring device; Step 5: Weigh and mix 84 alumina clinker with a particle size of ≥0.088 mm, fused white corundum with a particle size of ≥0.045 mm, activated alumina powder with a particle size of ≥3 um, and CA-70 aluminate cement with a particle size of ≥0.074 mm according to the above ratio, add the remaining half of sodium tripolyphosphate and silicon powder with a particle size of ≥5 um, and mix in a premixer for 2 minutes; Step 6: Add the fine powder matrix premixed in step 5 to the stirring device in step 4, add an appropriate amount of pure tap water and stir for 2 minutes to obtain a working layer mixture; Step 7: Pour the material obtained in step 6 into the mold to 1 / 2 capacity, and vibrate to form it as the working layer. Step 8: Pour the material obtained in step 3 into the remaining 1 / 2 capacity of the mold and vibrate it into shape to serve as a heat-insulating layer.

[0029] Step nine, drying at 130°C for 24 hours to obtain the multi-layer composite prefabricated brick with ceramic burner for hot blast furnace.

[0030] Example 3

[0031] The added weight proportions of the raw materials of the present invention are: 40 parts of 45 alumina clinker, 10 parts of coke gemstone, 20 parts of 84 alumina clinker, 5 parts of fused white corundum, 5 parts of andalusite, 10 parts of clay waste brick powder, 0.5 parts of primary clay powder, 5 parts of silica powder, 3 parts of CA-50 aluminate cement, 1 part of activated alumina powder, 0.5 parts of CA-70 aluminate cement, and the added amount of sodium tripolyphosphate is 0.02% of the total weight of the raw materials.

[0032] The particle size of 84 alumina clinker is a mixture of 8-5mm, 3-1mm and ≥0.088mm, and the mixing ratio is 1:1:1.

[0033] The particle size of fused white corundum is a mixture of 5-3mm and ≥0.045mm, with a mixing ratio of 2:1.

[0034] The preparation method of the ceramic burner multilayer composite prefabricated brick for hot blast furnace of the present invention is as follows: Step 1: Weigh and mix 45 alumina clinker with a particle size of 8-4mm and coke gemstone with a particle size of 4-0mm according to the above ratio, and put them into the mixing equipment; Step 2: Weigh and mix the clay waste brick powder with a particle size of ≥0.088 mm, the first-class clay powder with a particle size of ≥0.088 mm, and the CA-50 aluminate cement with a particle size of ≥0.074 mm according to the above proportions, add half of the sodium tripolyphosphate and the silicon micropowder with a particle size of ≥5 um according to the above proportions, and mix in a premixer for 1 minute to obtain a fine powder mixture; Step 3: Add the fine powder mixture obtained in step 2 to the stirring device in step 1, add tap water and stir for 1 minute to obtain a mixture for the insulation layer; Step 4: Weigh and mix 84 alumina clinker with a particle size of 8-5mm, fused white corundum with a particle size of 5-3mm, 84 alumina clinker with a particle size of 3-1mm, and andalusite with a particle size of 1-0mm according to the above proportions, and put them into a stirring device; Step 5: Weigh and mix 84 alumina clinker with a particle size of ≥0.088 mm, fused white corundum with a particle size of ≥0.045 mm, activated alumina powder with a particle size of ≥3 um, and CA-70 aluminate cement with a particle size of ≥0.074 mm according to the above ratio, add the remaining half of sodium tripolyphosphate and silicon powder with a particle size of ≥5 um, and mix in a premixer for 2 minutes; Step 6: Add the fine powder matrix premixed in step 5 to the stirring device in step 4, add an appropriate amount of pure tap water and stir for 2 minutes to obtain a working layer mixture; Step 7: Pour the material obtained in step 6 into the mold to 1 / 2 capacity, and vibrate to form it as the working layer. Step 8: Pour the material obtained in step 3 into the remaining 1 / 2 capacity of the mold and vibrate it into shape to serve as a heat-insulating layer.

[0035] Step nine, drying at 150°C for 24 hours to obtain the multi-layer composite prefabricated brick with ceramic burner for hot blast furnace.

[0036] The laboratory test indicators of the refractory materials obtained in Examples 1-3 are shown in Table 1. The refractory product sample preparation method adopts GB / T7321, the bulk density and apparent porosity test method adopts GB / T2997, the chemical analysis adopts GB / T6900, the room temperature compressive strength adopts GB / T5072.1, the heating permanent linear change adopts GB / T5988, and the load softening temperature adopts YB / T370.

[0037]

[0038] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-layer composite prefabricated brick for a hot blast stove with ceramic burners, characterized in that: It is divided into a working layer and an insulation layer, and the added weight portions are: 30-40 parts of 45 alumina clinker, 10-20 parts of coke gemstone, 20-50 parts of 84 alumina clinker, 5-20 parts of fused white corundum, 1-10 parts of andalusite, 1-10 parts of clay waste brick powder, 0.2-0.5 parts of first-grade clay powder, 1-5 parts of silica powder, 1-10 parts of CA-50 aluminate cement, 0.5-1 parts of activated alumina powder, 0.3-0.5 parts of CA-70 aluminate cement, and the added amount of sodium tripolyphosphate is 0-0.02% of the total weight of the original material.

2. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of 45 alumina clinker is 8-4mm, of which the weight fraction of Al2O3 is ≥45%; the particle size of 84 alumina clinker is a mixture of 8-5mm, 3-1mm and ≥0.088mm, with a mixing ratio of 1:1:1, of which the weight fraction of Al2O3 is ≥84%.

3. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of clay waste brick powder is ≥0.088mm, and the weight fraction of Al2O3 is ≥50%.

4. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of the primary clay powder is ≥0.088 mm, and the weight fraction of Al2O3 is ≥50%.

5. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of CA-50 aluminate cement is ≥0.074 mm, and the weight fraction of Al2O3 is ≥50%; The particle size of CA-70 aluminate cement is ≥0.074 mm, and the weight fraction of Al2O3 is ≥70%.

6. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of the activated alumina powder is ≥3μm, and the weight fraction of Al2O3 is ≥99.5%.

7. The multi-layer composite prefabricated brick for a hot blast stove according to claim 1, characterized in that: The particle size of silicon micropowder is ≥5μm.

8. The method for preparing a multi-layer composite prefabricated brick for a hot blast stove ceramic burner according to claim 1, characterized in that: Step 1: Weigh and mix 45 alumina clinker with a particle size of 8-4mm and coke gemstone with a particle size of 4-0mm according to the above ratio, and put them into the mixing equipment; Step 2: Weigh and mix the clay waste brick powder with a particle size of ≥0.088 mm, the first-grade clay powder with a particle size of ≥0.088 mm, and the CA-50 aluminate cement with a particle size of ≥0.074 mm according to the above proportions, add half of the sodium tripolyphosphate and the silicon micropowder with a particle size of ≥5 um according to the above proportions, and mix in a premixer for 1-2 minutes to obtain a fine powder mixture; Step 3: Add the fine powder mixture obtained in step 2 to the stirring device in step 1, add tap water and stir for 1-2 minutes to obtain a mixture for the insulation layer; Step 4: Weigh and mix 84 alumina clinker with a particle size of 8-5mm, fused white corundum with a particle size of 5-3mm, 84 alumina clinker with a particle size of 3-1mm, and andalusite with a particle size of 1-0mm according to the above proportions, and put them into a stirring device; Step 5: Weigh and mix 84 alumina clinker with a particle size of ≥0.088mm, fused white corundum with a particle size of ≥0.045mm, activated alumina powder with a particle size of ≥3um, and CA-70 aluminate cement with a particle size of ≥0.074mm according to the above proportions, add the remaining half of sodium tripolyphosphate and silicon powder with a particle size of ≥5um, and mix in a premixer for 1-2 minutes; Step 6: Add the fine powder matrix premixed in step 5 to the stirring device in step 4, add an appropriate amount of pure tap water and stir for 1-2 minutes to obtain a working layer mixture; Step 7: Pour the material obtained in step 6 into the mold to 1 / 2 capacity, and vibrate to form it as the working layer. Step 8: Pour the material obtained in step 3 into the remaining 1 / 2 capacity of the mold and vibrate it to form a heat-insulating layer. Step nine, drying at 100-150°C for 24 hours to obtain the ceramic burner multi-layer composite prefabricated brick for hot blast furnace.